Integrin-targeted nano-sized polymeric systems for paclitaxel conjugation: a comparative study. (26th November 2017) - Eldar-Boock, Anat; Blau, Rachel; Ryppa, Claudia; Baabur-Cohen, Hemda; Many, Ariel; Vicent, María Jesús; Kratz, Felix; Sanchis, Joaquin; Satchi-Fainaro, Ronit
Abstract: The generation of rationally designed polymer therapeutics via the conjugation of low molecular weight anti-cancer drugs to water-soluble polymeric nanocarriers aims to improve the therapeutic index. Here, we focus on applying polymer therapeutics to target two cell compartments simultaneously – tumour cells and angiogenic endothelial cells. Comparing different polymeric backbones carrying the same therapeutic agent and targeting moiety may shed light on any correlation between the choice of polymer and the anti-cancer activity of the conjugate. Here, we compared three paclitaxel (PTX)-bound conjugates with poly-l -glutamic acid (PGA, 4.9 mol%), 2-hydroxypropylmethacrylamide (HPMA, 1.2 mol%) copolymer, or polyethyleneglycol (PEG, 1:1 conjugate). PGA and HPMA copolymers are multivalent polymers that allow the conjugation of multiple compounds within the same polymer backbone, while PEG is a bivalent commercially available Food and Drug Administration (FDA)-approved polymer. We further conjugated PGA–PTX and PEG–PTX with the integrin αv β3 -targeting moiety RGD (5.5 mol% and 1:1 conjugate, respectively). We based our selection on the overexpression of integrin αv β3 on angiogenic endothelial cells and several types of cancer cells. Our findings suggest that the polymer structure has major effect on the conjugate's activity on different tumour compartments. A multivalent PGA–PTX–E-[c(RGDfK)2 ] conjugate displayed a stronger inhibitory effect on the endothelial compartment, showing a 50% inhibition of the migration of human umbilical vein endothelial cell cells, while a PTX–PEG–E-[c(RGDfK)2 ] conjugate possessed enhanced anti-cancer activity on MDA-MB-231 tumour cells (IC50  = 20 nM versus IC50 300 nM for the PGA conjugate).